UPAYA PERBAIKAN STATUS KESUBURAN LAHAN SAWAH TERDEGRADASI DENGAN PENAMBAHAN BAHAN ORGANIK - Slamet Minardi; Sri Hartati; Pardono Pardono (Caraka Tani: Journal of Sustainable Agriculture, 2012)
Deterioration or degradation of land is a phenomenon that occurs in many areas of cultivated land for agricultural cultivation. Incompatibility of land uses, such as soil excavation business excavation in wetland C for other purposes, is a cause soil damage. Former mining lands generally have physical properties, chemical and biological bad for plant growth, so that should be considered in its use, particularly to do with efforts t maintain soil fertility. The study, entitled “Improvements Efforts Rice Land Fertility Status Degraded With Addition of Organic Materials” aims to determine the effect of the use of organic matter in improving soil fertility in degraded wetland as well as the growth and yield of rice (Oryza sativa, L). the experiment was conducted in April to November 2011. This research is a pot experiment conducted at the Greenhouse Garden College of Agriculture Experiment UNS. Consist of 6 treatments namely P0: Control, P1: treatment of inorganic fertilizer/artificial as recommended, P2: the treatment of organic matter (manure), a dose of 5 to ha-1, P3: the treatment of organic material (fertilizer Bokashi), a dose of 5 ton ha-1, P4: the treatment of manure and inorganic fertilizer recommendation (50% : 50%) and P5: treatment Bokashi fertilizer and inorganic fertilizer recommendation (50% : 50%) and repeated four times and placed at random. Research using Complete Randomized Design (CRD) a single factor. The observation variables were observed: 1. Independent variables: a. Without treatment of organic fertilizer (using inorganic fertilizer recommended) b. Treatment of manure and fertilizer materials Bokashi (dose f 5 to ha-1), 2. Dependent variable: A variable is a variable bound observations of soil chemical properties (properties that are used as a determinant of soil fertility), which consist: soil pH, soil organic matter content (organic C), base saturation (KB), cation exchange capacity (CEC) and P-available soil. As well as the growth and yield of rice plants. The results showed that administration of organic fertilizers can increase soil fertility of degraded fields, proved to increase growth and yield of rice, such as plant height, dry weight, brangkasan above, the number of tillers in the treatment of organic material (fertilizer Bokashi) were harvested for grain yield and yield dry weight 1000 highest seed obtained in the treatment of manure and inorganic fertilizer recommendation (50% : 50%) compared with other treatments especially compared with controls.